MIDWIFERY CARE CONTINUITY OF CARE FOR MRS. M, 31 YEARS OLD, G1P0A0, 33/34 WEEKS GESTATION, SINGLE LIVE FETUS WITH BREECH PRESENTATION + GRADE 2 OBESITY + CPD + DISABILITY (SPEECH IMPAIRMENT) AT RSIA PURA RAHARJA SURABAYA CITY - Permatasari, Ikke; Yuliatin, Nur Linda; Ningse, Tri Muliati (PT. Antis International Publisher, 2025)
Objective: This study aims to provide Continuity of Care (COC) midwifery services for pregnant, laboring, postpartum women, newborns, and family planning clients, ensuring comprehensive and sustainable care, particularly for cases with complex conditions. Method: A descriptive case study approach was employed, utilizing primary and secondary data collected through interviews, observations, examinations, and documentation reviews, analyzed according to midwifery care management. The case involved Mrs. M, a 31-year-old primigravida at 33/34 weeks of gestation with a breech presentation, grade 2 obesity, cephalopelvic disproportion (CPD), and speech impairment, conducted at RSIA Pura Raharja, Surabaya, starting December 9, 2024. Results: The implementation of COC midwifery care facilitated continuous monitoring and comprehensive management of Mrs. M's condition, improving maternal and fetal health outcomes while fostering trust and satisfaction in healthcare services. Novelty: This study highlights the integration of evidence-based midwifery care tailored for pregnant women with disabilities, emphasizing the role of COC in enhancing maternal and neonatal health while contributing to the reduction of maternal and infant mortality rates.